2016
DOI: 10.18553/jmcp.2016.22.5.467
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Change in Adherence Status from 1 Year to the Next Among Patients with Type 2 Diabetes Mellitus on Oral Antidiabetes Drugs

Abstract: Funding for this research was provided by Eli Lilly and Company. Comprehensive Health Insights, owned by Humana, completed this study. Peng, Fu, Ascher-Svanum, Ali, and Rodriguez are employees of Eli Lilly and Company. Saundankar and Louder are employed by Comprehensive Health Insights, and Slabaugh and Young are employed by Humana. Study concept and design were contributed by Peng, Ascher-Svanum, and Young. Saundankar and Louder took the lead in data collection, while Saundankar, Peng, Fu, and Louder interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…A recent analysis of the present cohort determined that those non-adherent to OADs in the first year of therapy had a high likelihood of remaining non-adherent in the second year [28]. Similar results were observed in a recent study of antidiabetes medication adherence across multiple years [29]. Taken together, these findings suggest that medication non-adherence is a behaviour that is challenging to correct once established; consequently, providers should work with patients from the onset of therapy to ensure that barriers to adherence are identified and removed in order to limit the impact of this behaviour on poor future outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…A recent analysis of the present cohort determined that those non-adherent to OADs in the first year of therapy had a high likelihood of remaining non-adherent in the second year [28]. Similar results were observed in a recent study of antidiabetes medication adherence across multiple years [29]. Taken together, these findings suggest that medication non-adherence is a behaviour that is challenging to correct once established; consequently, providers should work with patients from the onset of therapy to ensure that barriers to adherence are identified and removed in order to limit the impact of this behaviour on poor future outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…Only approximately one‐fourth of patients for whom HbA1c data were available reached desired treatment targets at the end of the follow‐up period, despite changes in treatment regimens for most patients. Changes in therapy may fail to have a positive impact because of factors such as treatment adherence, clinical characteristics, treatment‐related costs and access to care . Hypoglycaemia was common and occurred at least once in half the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…3). Saundankar et al has recently experienced problems with low medication adherence and suspension of regular clinic visits, especially among young patients with type 2 diabetes [30]. Similarly, a recent study using an online survey of Japanese patients with type 2 diabetes found that younger patients (under 65 years old) tended to prefer once-weekly oral administration compared with older patients, primarily because the younger patients found it less burdensome not to have to take pills every day, and felt that they would be less likely to forget to take a weekly medication [31].…”
Section: Discussionmentioning
confidence: 99%